INFLASI TERHADAP KEMISKINAN PAPUA BARAT - Elina Relawaty Situmorang; Johny Aninam; La Ode Alisyah (Lensa Ekonomi, 2025)
This study aims to analyze the relationship between inflation and poverty levels in West Papua Province prior to the establishment of Southwest Papua, covering the period 2010–2019. West Papua is one of the provinces in Indonesia with persistently high inflation and poverty rates, making it a relevant case for regional economic analysis. This research employs a descriptive quantitative approach using secondary data on inflation and poverty obtained from Statistics Indonesia (BPS) and Bank Indonesia. The analysis is conducted through data tabulation and comparative assessment between West Papua, Papua Province, and the national average. The results indicate that West Papua consistently experienced inflation and poverty levels above the national average during the study period. High inflation potentially exacerbated poverty by reducing the purchasing power of low-income households, particularly in regions with structural economic constraints. These findings highlight the importance of inflation control policies that are sensitive to regional disparities and integrated with poverty reduction strategies. Future studies are recommended to apply econometric methods to quantify the magnitude of inflation’s impact on poverty more precisely.